2018
DOI: 10.1371/journal.pone.0198185
|View full text |Cite
|
Sign up to set email alerts
|

Association between handgrip strength, balance, and knee flexion/extension strength in older adults

Abstract: The objective of the study was to examine the association between handgrip strength (HGS), knee flexion and extension strength, and static and dynamic balance in older women. One hundred and ten women with a mean age of 67.4±5.9 years were assessed for dynamic postural balance using the Time Up & Go Test (TUG) with and without cognitive tasks. Semi-static balance was assessed by means of a force platform; knee flexor and extensor muscle strength was calculated using an isokinetic dynamometer; and HGS using a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(59 citation statements)
references
References 23 publications
2
52
0
5
Order By: Relevance
“…In this study, we reported a poor association between hand grip strength and measures of knee extensor and flexor strength in a community-dwelling sample of older men. Our results are consistent with the low to fair relationships between hand grip strength and lower extremity strength observed in large population-based studies involving older cohorts [ 14 , 35 , 36 ]. Yeung et al [ 37 ] also found only low to moderate agreement between hand grip strength and knee extension strength independently of age and health status in populations of both young and older patients.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, we reported a poor association between hand grip strength and measures of knee extensor and flexor strength in a community-dwelling sample of older men. Our results are consistent with the low to fair relationships between hand grip strength and lower extremity strength observed in large population-based studies involving older cohorts [ 14 , 35 , 36 ]. Yeung et al [ 37 ] also found only low to moderate agreement between hand grip strength and knee extension strength independently of age and health status in populations of both young and older patients.…”
Section: Discussionsupporting
confidence: 91%
“…80 Cross-sectional evidence from 110 women aged 67.4 ± 5.9 years indicated that HGS on the dominant (r = -0.20; p = 0.03) and non-dominant hand (r = -0.20; p = 0.03) is correlated with the timed-up-and-go test. 81 The 6-min walk test is a popular method for assessing physical functioning and fitness. 82 Martín-Ponce et al 83 found that adults aged at least 60 years who were in the lower HGS category walked a shorter distance (84.3 ± 12.0 m) on the 6-min walk test than those in the higher HGS category (178.0 ± 14.0 m; p < 0.001).…”
Section: Hgs and Dynamic Assessments Of Functionmentioning
confidence: 99%
“…Other authors have also reported an association between lower-limb strength-including isometric knee extension-and handgrip strength [21]. Moreover, Alonso et al [36] recently reported that handgrip strength was not only related to knee extension strength, but also to TUG performance and dynamic balance in older adults. Similarly, handgrip strength has been reported to be correlated with ambulatory capacity in frail older adults [37].…”
Section: Discussionmentioning
confidence: 94%